PENGAUDITAN SISTEM INFORMASI MANAJEMEN DALAM MENUNJANG PENGIRIMAN MAKANAN UNTUK KEMAJUAN PERUSAHAAN - ANTONI, JUFRI (JURNAL ILMIAH KOHESI, 2024)
This research addresses the issue of efficiency and accuracy in order and transaction management in the culinary industry. The main problems faced are long service times and high error rates in ordering, which have a negative impact on customer satisfaction and operational costs. To address these issues, this research developed an integrated Android-based self-service application. The solution offered through this application includes inventory monitoring features, automatic payment processing, and real-time sales reporting. The research method used involved developing and testing the application with a quantitative approach. The objectives of this research are to improve the restaurant's operational efficiency, reduce ordering errors, and increase customer satisfaction. The contribution of this research is the development of an application that can be a valuable reference for the development of food self-service technology in the future. Interim results show that this application can increase service time efficiency by 25% and reduce ordering errors by 15%. The implementation of this self-service technology is expected to help culinary companies compete more effectively in an increasingly competitive industry.